2016
DOI: 10.1177/0886260516645574
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adjustment Among Rural Adolescents Exposed to Family Violence

Abstract: This study examines differences in psychological adjustment in a sample of rural adolescents who have been exposed to family violence. Self-report questionnaires were administered to 580 adolescents and their primary caregivers. The results revealed that over two thirds of the study participants (68.8%) had been exposed to violence in their families. As hypothesized, cluster analysis identified several profiles among adolescents, distinguished by their psychological and emotional functioning: well adjusted (46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
(113 reference statements)
1
9
0
Order By: Relevance
“…Similar to our study, other studies identify three groups of students based on interpersonal values (Gázquez et al, 2015a(Gázquez et al, ,b, 2016 or three adjustment groups (Spilsbury et al, 2008;McDonald et al, 2016;Sianko et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our study, other studies identify three groups of students based on interpersonal values (Gázquez et al, 2015a(Gázquez et al, ,b, 2016 or three adjustment groups (Spilsbury et al, 2008;McDonald et al, 2016;Sianko et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…This study was part of the (ADVS) (cf. Hedge, Sianko, & McDonell (); Sianko, Hedge, & McDonell (), a 4‐year cohort sequential research initiative that examined the developmental trajectory of dating violence victimization and perpetration among adolescents in the rural South. Data were collected in four annual waves, from 2012 to 2015, using student and caregiver surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Research in the past two decades has revealed that young persons who have experienced childhood exposure to IPV use a variety of coping strategies to adapt to this traumatic experience, leading to unique developmental outcomes (Cameranesi, Piotrowski, & Brownridge, 2020). To cope with IPV exposure, young persons use some coping strategies that can be considered ineffective as they increase their vulnerability to developing maladapting behaviors and adjustment difficulties involving emotional problems (e.g., depressive and post-traumatic stress disorder (PTSD) symptoms), school problems, conduct problems, rule-breaking and risk-taking behaviors, aggressive behavior, and relational problems (Doucet & Fortin, 2014;Grogan-Kaylor, Stein, Clark, Galano, & Graham-Bermann, 2017;Piotrowski, 2011;Sianko, Hedge, & McDonell, 2016). However, young persons exposed to IPV use also coping strategies that enable them to effectively adapt to the traumatic experience of growing up in an IPV-affected family.…”
Section: Introductionmentioning
confidence: 99%